Perception and cognition in language and culture - Aĭkhenvalʹd, A. I͡U. (Aleksandra I͡Urʹevna); Storch, Anne (Brill's studies in language, cognition and culture, 2013)
Every language has a way of talking about seeing, hearing, smelling, tasting and touching. This can be done through lexical means, and through grammatical evidentials. The studies presented here focus on the experssions of perception and cognition in languages of Africa, Oceania, and South America.